Makna Khitan Perempuan di Desa Sipayo Perspektif Hadis Nabi saw - Inadjo, Susanti; Kara, Siti Aisyah; Puyu, Darsul S. (MERCUSUAR : Jurnal Komunikasi dan Penyiaran Islam, 2021)
Symbols in communication traditions hold very profound meanings, generally symbols are used to represent the intended meaning, not only that, but symbols in semiotics are also referred to as signs that refer to something else. Especially in the Mungubingo traditional ceremony that uses symbols to communicate these meanings. This study aims to see the meaning in symbols that exist in the Mungubingo traditional ceremony in relation to the practice of female circumcision, and how female circumcision in the tradition is seen in the perspective of hadith. The results of the study found that hadiths about female circumcision are divided into two categories. The first category is authentic hadiths, but their contents do not show circumcision for females. The second category is weak hadiths that cannot be used as an argument in establishing laws for female circumcision. This study found that the appropriate law is permissible, depending on the executor and its implementation.